The new Aristotelian essentialists - Noonan, Harold (De Gruyter, 2018)
In recent years largely due to the seminal work of Kit Fine and that of Jonathan Lowe there has been a resurgence of interest in the concept of essence and the project of explaining de re necessity in terms of it. Of course, Quine rejected what he called Aristotelian essentialism in his battle against quantified modal logic. But what he and Kripke debated was a notion of essence defined in terms of de re necessity. The new Aristotelian essentialists regard essence as entailing but prior in the order of explanation to de re necessity. In what follows I argue that the concept of essence so understood has not been adequately explained and that any attempt to explain it, at least along the lines most familiar from the literature, must be flagrantly circular or make use of de re modal notions.